Chomsky's Theory and Teaching Arabic for Special Purposes - Hezam, Motea Naji Dabwan; Mardani, Dadan; Syafei, Isop (Ukazh: Journal of Arabic Studies, 2025)
This study aims to examine the characteristics of Arabic language instruction for specific purposes (ASP), assess the applicability of Noam Chomsky’s generative grammar theory within this context, and explore the major challenges faced in both Arab and non-Arab environments. Employing a qualitative-descriptive method with an inductive approach, the study is grounded in a literature review and critical analysis of instructional materials. The findings reveal that ASP instruction is marked by needs-based analysis, a strong emphasis on communicative competence, methodical flexibility, and specialized lexical-syntactic integration. Chomsky’s theory is shown to align with the ASP framework, as it promotes sentence generation capabilities over rote memorization. Nevertheless, the implementation faces multiple obstacles, including the lack of thematic textbooks, insufficient teacher training, diglossia, and the tendency to neglect cultural context in curriculum design. The study concludes with recommendations to develop Arabic language programs that are more responsive, context-driven, and linguistically sound.